Austronesian Soundscapes Performing Arts in Oceania and Southeast Asia - Abels, Birgit 1980- (IIAS Publications, 2012)
In Austronesia-the region that stretches from Madagascar in the west to Easter Island in the east-music plays a vital role in both the construction and expression of social and cultural identities. Yet research into the music of Austronesia has hitherto been sparse. Drawing together contemporary cultural studies and musical analysis, Austronesian Soundscapes will fill this research gap, offering a comprehensive analysis of traditional and contemporary Austronesian music and, at the same time, investigating how music reflects the challenges that Austronesian cultures face in this age of globalization